Modelling of a filtration of subsoil waters in built up territories іn view of influence of deep foundation ditches - Соколовська, В.А. (Proceedings of National Aviation University (archive), 2004)
Influence of deep foundation ditches on dynamics(changes) of subsoil waters in borders of building is analysed. The basic equations for modelling processes which occur in грунтах the bases are given.